Hybrid Recommendation Engine with Web Scraping and Sentiment Analysis - Sontakke, N; Sabarinath, S; Sangamnerkar, S; Iyer, V (International Journal of Computer Sciences and Engineering, 2025)
In recent years a lot of data has been generated owing to the exponential increase in internet usage. People are overloaded with information, spanning over multiple domains. This helps people obtain knowledge and come to informed decisions. If we consider purchasing a product as a use case, the buyer can visit multiple websites to find strengths and weaknesses of the product as well as the opinions of other purchasers. To make this process easier and faster for the buyer we propose a robust and scalable hybrid recommendation system which is implemented as a combination of Content Based Recommendation System and Collaborative Filtering Techniques. As a test case, this system has been used to help purchase smartphones based on all features and sentiments of previous purchasers. System gets data using a self-learning web crawler that gathers data from a number of relevant websites irrespective of their different structures. The sentiments of users who purchased the same items previously have also been analyzed to aid the current buyers‟ decisions. In this paper, we have provided detailed survey and comparison of multiple techniques we reviewed before implementing each module